KINERJA GURU BAHASA ARAB DALAM PENGEMBANGAN BAHAN AJAR PADA MADRASAH ALIYAH DI PAREPARE - Saepudin Saepudin (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
Material development is one of the competencies that should be required by Arabic teacher in their duties. It is important for them to make the teaching and learning process more effective and efficient. In fact, many teacher pay less attention to their duties. This research is a descriptive-qualitative. The subjects of the research were Arabic teachers of public and private Madrasah Aliyah. Data was collected through interviews, observation, documentation, and triangulation. The Arabic material development of MA teachers in Parepare were, reduction, simple adaptation and modifications, addition of sharf and qawaid. The problems faced by Arabic teacher at Madrasah Aliyah in Parepare are a low student motivation in learning Arabic, variety of Arabic language ability, lack of cost and infrastructure. To overcome these problems, the teachers are encouraged to participate actively in Congress of Subject Teacher (MGMP), teachers are motivated to take part in training or workshop relating to the improvement of learning and teaching materials, the teachers motivate students to interact with the Arabic language, the teachers usually adjust the material to the students' abilities, and teachers delivers teaching materials with various techniques.